Правило уравнений

Правило уравнений

. $$\sqrt{x^{2}-x} + \sqrt{2 — x — x^{2}} = \sqrt{x} — 1$$

. . .
, : $$\left\{ \begin{array}{l}
x^2 — x \ge 0 \\
2 — x — x^2 \ge 0 \\
x \ge 0
\end{array} \right.\, \Leftrightarrow \left\{ \begin{array}{l}
x \in \left( { — \infty ;0} \right] \cup \left[ {1; + \infty } \right) \\
x \in \left[ { — 2;1} \right] \\
x \in \left[ {0; + \infty } \right)
\end{array} \right.\, \Leftrightarrow \left[ \begin{array}{l}
x = 0 \\
x = 1
\end{array} \right.$$

, . , . , , . , x = 0 , x = 1 − .

. 1.

, , . , , $$\sqrt {f(x)} = g(x)\, \Leftrightarrow \left\{ \begin{array}{l}
g(x) \ge 0, \\
f(x) = g^2 (x)
\end{array} \right.$$

g (x) ? 0 . , g (x) , , , x g (x) ? 0.



Источник: uztest.ru


Добавить комментарий